Memahami Transformasi Pendidikan Luar Sekolah: Analisis Empiris Dampak Program PKBM Al-Madinah Kediri melalui Pendekatan Fenomenologi - Abdurochman, Abdurochman; Supriyono, Supriyono; Dayati, Umi; Desyanty, Ellyn Sugeng (Jurnal Simki Pedagogia, 2024)
Non-formal education (NFE) is a form of education outside the formal system, which provides services to certain target students in the fields of social, religious, cultural, skills, and expertise. One of the institutions that organise NFE is the Al-Madinah Kediri Community Learning Centre (CLC), which offers a free equivalency education programme for children and adults. This study aims to understand the transformation experienced by CLC Al-Madinah Kediri students after attending the equivalency education programme. This research uses a phenomenological approach, which seeks to uncover the meaning and essence of learners' life experiences from their own perspective. This research was conducted using in-depth interviews with 10 learners who have completed the Paket B (junior high school equivalent) or Paket C (senior high school equivalent) programme at CLC Al-Madinah Kediri. The results showed that learners of CLC Al-Madinah Kediri experienced transformation in the aspects of knowledge, skills, attitudes, values, and opportunities. Learners feel more confident, independent, empowered, and contribute to society after participating in the equivalency education programme. Learners also get other benefits, such as dormitory facilities, meals, pocket money, and guidance from the foundation. This research implies that NFE can be an effective and relevant alternative in fulfilling the lifelong education needs of disadvantaged communities.